Haida totem poles, Klink wan, Alaska, ca. 1904 - Case, W. H. (William Howard), 1868-1920
Four Haida totem poles, Klink wan Alaska, ca. 1898-1910. Totems in front of several houses, other buildings including church in background. Caption on image: Totems at Old Kling-Wan, Alaska. W. H. Case, 166-N Notes from unidentified sources: Kaijani Haida village showing poles, dwellings and church. PH Coll 300.24